No Association of Variants of the NPY-System With Obsessive-Compulsive Disorder in Children and Adolescents - Maximilian Franke; Annette Conzelmann; Edna Grünblatt; Anna M. Werling; Helen Spieles; Christoph Wewetzer; Andreas Warnke; Marcel Romanos; Susanne Walitza; Tobias J. Renner; Tobias J. Renner (Frontiers in Molecular Neuroscience, 2019)
Obsessive-compulsive disorder (OCD) causes severe distress and is therefore counted by the World Health Organisation (WHO) as one of the 10 most impairing illnesses. There is evidence for a strong genetic underpinning especially in early onset OCD (eoOCD). Though several genes involved in neurotransmission have been reported as candidates, there is still a need to identify new pathways. In this study, we focussed on genetic variants of the Neuropeptide Y (NPY) system. NPY is one of the most abundant neuropeptides in the human brain with emerging evidence of capacity to modulate stress response, which is of high relevance in OCD. We focussed on tag-SNPs of NPY and its receptor gene NPY1R in a family-based approach. The sample comprised 86 patients (children and adolescents) with eoOCD with both their biological parents. However, this first study on genetic variants of the NPY-system could not confirm the association between the investigated SNPs and eoOCD. Based on the small sample size results have to be interpreted as preliminary and should be replicated in larger samples. However, also in an additional GWAS analysis in a large sample, we could not observe an associations between NPY and OCD. Overall, these preliminary results point to a minor role of NPY on the stress response of OCD.